Significant promotion effect of carbon nanotubes on the electrocatalytic activity of supported Pd NPs for ethanol oxidation reaction of fuel cells: the role of inner tubes - Zhang, Jin; Cheng, Yi; Lu, S.; Shen, P.; Jiang, San Ping (The Royal Society of Chemistry, 2014)
The inner tubes of carbon nanotubes (CNTs) have a significant promotion effect on the electrocatalytic activity of Pd nanoparticles (NPs) for the ethanol oxidation of direct alcohol fuel cells (DAFCs) and Pd NPs supported on CNTs with 3–7 walls show a much higher activity as compared to that supported on typical single-walled and multi-walled CNTs.